PENGUATAN LITERASI DIGITAL DAN KESADARAN HAK CIPTA BAGI KOMUNITAS SENI TRADISI DI ERA DIGITAL - Putri, Martina Shalaty (Gapenas Publisher, 2025)
The program was initiated in response to the challenges faced by Ayodya Pala, a traditional arts foundation, in adapting to the digital transformation, particularly regarding the use of social media for artistic promotion and the protection of intellectual property rights. The project began with a needs assessment through interviews and discussions with the foundation’s trainers and management, followed by the development of context-based materials focusing on digital literacy, ethical communication, and copyright awareness. The core activity consisted of a one-day session involving 27 participants, delivered through lectures and participatory discussions. The first session covered key concepts of digital literacy, including ethical behavior in online spaces, digital citizenship, and strategic use of social media. The second session addressed digital rights and responsibilities, emphasizing copyright as a fundamental aspect of digital culture, especially in the context of sharing and producing creative content. Evaluation results showed a significant improvement in participants’ understanding: 92% reported better comprehension of digital literacy, and 100% recognized the importance of copyright in digital environments. While only 37% of participants had previously applied copyright protection practices, many expressed a new awareness and commitment to attribution and ethical content sharing. This program successfully laid a foundation for a more responsible and informed digital presence within the traditional arts community and highlighted the need for further support in the form of practical digital capacity-building initiatives..